PENGARUH PDRB PER KAPITA, JUMLAH PENDUDUK YANG BEKERJA, INFLASI TERHADAP PAD KOTA DENPASAR - Astawa, I Gede Ngurah; Budhi, Made Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 11 (2022): vol.11.11. NOVEMBER 2022[4011-4233], 2022)
The purpose of this study was to analyze the effect of Regional Gross Domestic Product per Capita, Number of Working Population, and Inflation simultaneously and partially effect on Regional Original Income of Denpasar City by using multiple linear regression analysis technique. The results of this study state that 1) Gross Regional Domestic Product per Capita, Number of Working Population and Inflation simultaneously have a significant effect on Regional Original Income of Denpasar City, 2) Gross Regional Domestic Product per Capita have a significant positive effect on Regional Original Income of Denpasar City, 3) The number of working population does not have a partial significant effect on the Regional Original Income of the City of Denpasar, 4) Inflation does not have a partial significant effect on the Regional Original Income of the City of Denpasar. Keywords: Regional Original Income, Gross Regional Domestic Product per Capita, Number of Working Population, inflation